Analisis Kadar Biomarker Urine Monocyte Chemoattractant Protein-1 Terhadap Klasifikasi Histopatologi Nefritis Lupus - Yuliana Salman; STIKES Husada Borneo Banjarbaru (HB PRESS, 2013)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by chronic and acute inflammation. The common of serious complications in SLE is lupus nephritis.. Biomarker that showed high specificity for SLE especially in lupus nephritis is Monocyte Chemoattractant Protein urine-1 (uMCP-1). In Indonesia, correlation between uMCP-1 with lupus nephritis still unknown. This approach is expected to replace renal biopsy in histopathological classification of lupus nephritis. This study is an observational that was conducted in cross-sectional study. The research will be conducted over a 11-month with urine sampling to determine levels of MCP-1 in patients with SLE, and renal biopsy was performed to determine the class of lupus nephritis according to WHO (1982) classification. The results showed no significant difference (p = 0,247>α) between mean rank levels of urinary uMCP-1of control and cases group. In the Kruskal-Wallis test demonstrated the comparison of mean rank urine MCP-1 levels among 3 groups are no significant difference (p = 0,197>α). It can be concluded that the levels of urinary MCP1 was not associated with incidence and histopathological classification of lupus nephritis.